Utilization and breeding perspective in the egusi gourd Melothria sphaerocarpa (Cogn.) H. Schaef. et S.S. Renner (syn: Cucumeropsis mannii Naudin) - Houdégbé, Carlos A.; Sogbohossou, E. O. Dêêdi; Achigan-Dako, Enoch Gbenato (My University, 2016)
Melothria sphaerocarpa (egusi gourd) is an economically important cucurbit species cultivated only for its seeds in West and Central Africa but also found in South and Central America. The species is thought to originate from America and sister of wild relatives such as Melothria candolleana and Melothria campestris, which thrive in America only. The species is rich in nutrients and is a useful crop to ensure food and nutritional security. It also has several applications in industries for cooking oil, soap, paint and biodiesel production. However, the production of egusi gourd is declining because of its low yield, the requirement of stakes and the long production cycle. These bottlenecks lead to the substitution of egusi gourd by other sister egusi crops and increase the threat on the species. This review documents current knowledge for improving existing cultivars of egusi gourd to promote sustainable utilization. Breeding objectives may include developing early maturing, high yielding, as well as pests and diseases resistant varieties. Current in situ and ex situ conservation strategies need to be strengthened. Further investigations need to be carried out on the phylogeny and phylogeography of the genus Melothria, the genetic diversity among American and African populations, the reproductive biology and nutritional value. Utilization and breeding perspective in the egusi gourd Melothria sphaerocarpa... | Request PDF. Available from: https://www.researchgate.net/publication/290435461_Utilization_and_breeding_perspective_in_the_egusi_gourd_Melothria_sphaerocarpa_Cogn_H_Schaef_et_SS_Renner_syn_Cucumeropsis_mannii_Naudin [accessed Mar 07 2018].